The Concept of the Anti-Hero Character in the Movie The Mask (1994) - Shandina Marwa; Udayani Permanaludin; Yoga Sudarisman (LPPM Institut Pendidikan Nusantara Global, 2026)
This study explores the duality of the main character’s persona in The Mask (1994) by applying Christopher Vogler’s narrative framework within the context of film studies. The research aims to investigate the concept of the anti-hero as a recurring character type in modern narrative texts, particularly in cinematic works, where characters are defined by flawed attributes and ethically ambiguous behavior. The relevance of the anti-hero lies in its deviation from conventional heroic archetypes and its function as a representation of shifting public values and beliefs. This study employs a descriptive qualitative method using a narrative structuralism approach. The analysis draws on Christopher Vogler’s concept of the anti-hero and Eaton’s (2012) anti-hero theory to examine narrative elements within the film. The film’s narrative presents the main character through traits such as manipulative, cruel, petty, malicious, selfish, ill-tempered, and duplicitous behavior. Primary data consist of significant character interactions, dialogues, and visual representations in specific scenes, while secondary data are obtained from previous studies and relevant literature on anti-hero representation and heroic film theory. The findings indicate that the main character in The Mask successfully embodies the anti-hero archetype by critiquing everyday identity repression, releasing subconscious impulses, and disrupting social conformity through chaos. This study contributes to academic discussions on anti-hero characters by demonstrating how The Mask, beyond its cartoonish entertainment value, functions as a structural narrative text in which manipulative traits dominate the character’s transformation.